Organic electrochemical transistors as novel biosensing platforms to study the electrical response of whole blood and plasma. Issue 1 (6th December 2021) - Preziosi, Valentina; Barra, Mario; Tomaiuolo, Giovanna; D'Angelo, Pasquale; Marasso, Simone Luigi; Verna, Alessio; Cocuzza, Matteo; Cassinese, Antonio; Guido, Stefano
Abstract : In this paper, for the first time to the best of our knowledge, OECTs are employed to investigate the electrical response of human blood, plasma and alternative buffer solutions that inhibit red blood cell (RBC) aggregation. Abstract : In this paper, for the first time to the best of our knowledge, organic electrochemical transistors are employed to investigate the electrical response of human blood, plasma and alternative buffer solutions that inhibit red blood cell (RBC) aggregation. Our focus is on selecting a suitable electrolytic platform and the related operating conditions, where the RBC effect on the OECT response can be observed separately from the strong ionic environment of plasma in whole blood. The transient response of whole blood to pulse experiments is characterized by two time constants, which can be related to blood viscosity and to the capacitive coupling between the ionic and electronic components of the overall system. The role of capacitive effects, likely due to enhanced double-layer formation by negatively charged RBCs, is also confirmed by the increase of transconductance which was found in RBC suspensions as compared to the suspending buffer. Overall, the complex behavior found in these experiments provides new insights for the development of innovative blood-based sensing devices for biomedical applications.